What Experts Tell about Integrated Marketing Communication for Effective Business Promotion and Sale Strategy - Gunawan Widjaja (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The expert’s study about integrated marketing communications for promotion and sales strategies ineffective business activities is the main objective of this study. We address the core gap here through a literature review that addresses integrated marketing communications in sales and promotions in every business. We found data from more than 50 articles on the economics of marketing and business communications in sales and promotion. After we found the data, we studied it comprehensively under the phenomenological approach to finding findings or answers that were valid and believed to be valid. Because this study was carried out during the implementation of public mobility restrictions, we tried secondary data with a search system with the help of Google Scholar on several scientific publications such as Google book, Taylor, Sagepub, and Elsevier. Based on the existing data and discussion of the results, we conclude that a successful integrated marketing communication will establish a core message, emphasize the competitive advantage, address the right target market, and adapt the message to suit supporting media channels. The message is essentially the same across platforms, but the delivery mechanism varies.